2015
DOI: 10.1007/s00338-015-1294-y
|View full text |Cite
|
Sign up to set email alerts
|

Christmas tree worms of Indo-Pacific coral reefs: untangling the Spirobranchus corniculatus (Grube, 1862) complex

Abstract: Christmas tree worm is the common name of a group of colorful serpulid polychaetes from the genus Spirobranchus that are symbionts of hermatypic corals. As is increasingly common with reef-associated organisms, Spirobranchus is arranged as a complex of species with overlapping geographic ranges. Current species delimitations based largely on opercular morphology are problematic because of high intraspecific variation. Here, a multi-gene phylogeny of the Spirobranchus corniculatus complex, which tentatively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Several taxa were initially synonymized by ten Hove (1970) under S. tetraceros and a cosmopolitan distribution was hypothesized for this taxon, among other reasons because of its high opercular variation (see also Perry et al 2018). Ben-Eliahu and ten Hove (2011) and Willette et al (2015) also reported highly variable opercula for S. tetraceros specimens from the Suez Canal and the Indo-Pacific S. corniculatus, respectively. The molecular characterization of Valencia Port and Heraklion specimens carried out here, including specimens with either conical or fully-branched opercula, confirms that this morphological variation simply corresponds to intraspecific plasticity.…”
Section: Key To Mediterraneanmentioning
confidence: 92%
“…Several taxa were initially synonymized by ten Hove (1970) under S. tetraceros and a cosmopolitan distribution was hypothesized for this taxon, among other reasons because of its high opercular variation (see also Perry et al 2018). Ben-Eliahu and ten Hove (2011) and Willette et al (2015) also reported highly variable opercula for S. tetraceros specimens from the Suez Canal and the Indo-Pacific S. corniculatus, respectively. The molecular characterization of Valencia Port and Heraklion specimens carried out here, including specimens with either conical or fully-branched opercula, confirms that this morphological variation simply corresponds to intraspecific plasticity.…”
Section: Key To Mediterraneanmentioning
confidence: 92%
“…Recently, three species of the Indo-West Pacific Spirobranchus corniculatus complex, S. corniculatus, S. gaymardi (Quatrefages, 1866) and S. cruciger (Grube, 1862), were genetically analysed using nuclear and mitochondrial DNA markers which revealed a single, monophyletic clade for the S. corniculatus complex (Willette et al 2015). The authors found that "the genetic and morphological variation observed is not geographically based, indicating that the former S. corniculatus complex of three morphospecies is a single, morphologically variable species across the Central Indo-Pacific".…”
Section: )mentioning
confidence: 99%
“…26) Remarks. Based on analysis of nuclear and mitochondrial markers, Willette et al (2015) concluded that the Spirobranchus corniculatus-complex of morphospecies identifiable by their opercula mainly (see Smith 1985 for further differences), which includes Sp. corniculatus sensu stricto, Sp.…”
Section: Spiraserpula Snelliimentioning
confidence: 99%